School Location and Size as Predictors of Head Teachers’ Job Satisfaction - Ghazi, Safdar Rehman; Shahzada, Gulap (Richtmann Publishing, 2012)
The general intent of this descriptive study was to document the general job satisfaction of the head teachers workingin government elementary schools in context of their school location and size as measured by the Minnesota SatisfactionQuestionnaire (MSQ). Therefore, survey design was used to obtain needed information. The teachers of all categories who wereworking as head teachers in government elementary schools at district Toba Tek Singh (in any area, i.e., rural or urban) in thePunjab, Pakistan (except the sampled for pilot study), were asked to fill the questionnaire. The Urdu version of the modifiedMinnesota Satisfaction Questionnaire (MSQ) was used as a research tool in this study. It was concluded that the head teachersworking in government elementary schools at district Toba Tek Singh in the Punjab, Pakistan were found generally satisfied withtheir positions regardless of their school location and size. The head teachers working in urban areas were found significantlymore satisfied than the head teachers of rural areas, and no significant differences were found among the job satisfaction levelsof the head teachers working in smaller and larger schools. On the basis of the responses to the MSQ, it appears thatelementary school head teachers (Toba Tek Singh) in the Punjab, Pakistan were satisfied with their jobs. Policy makers andother concerned authorities should put forth effort to either maintain this level of satisfaction or increase it to a higher level. Thismay be done by increasing satisfaction for different aspects of job; Compensation, Working Conditions, Social Status, andSchool System Policies and Practices. There is need to improve the job satisfaction level of the government elementary schoolhead teachers working in rural areas of district Toba Tek Singh. This can be done while providing them some special facilities,incentives, and allowances, like better working conditions and transport or travelling allowance etc. Study on satisfaction andschool location should be conducted to investigate the reason why job satisfaction increases with urban schools and studies onsatisfaction to investigate more predictors to job satisfaction should be conducted.